Anemia como predictor de mal estado funcional neurológico a corto plazo en pacientes adultos hospitalizados por enfermedad cerebrovascular isquémica aguda - Vargas Chávez, Iris Jezabella (2020)
Objective: To determine if anemia is a predictor of poor neurological functional status in the short term in adult patients hospitalized for acute ischemic cerebrovascular disease. Materials and methods: A prospective analytical observational study in which 96 patients hospitalized for acute ischemic cerebrovascular disease were followed up in Hospital Regional Docente de Trujillo (HRDT) in the period 2017-2018. It was distributed to patients according to the presence or absence of anemia and functional status was recorded (using the modified Rankin scale) on the first and 14th day of admission, as well as sociodemographic, clinical and laboratory variables. Results: The average age of patients was 73 years. The prevalence of anemia at admission and poor functional status at 14 days was 41.6% and 66.6%, respectively. It was found that anemia increased the risk of presenting poor functional status 2.18 times more than patients without anemia (RR: 2.184, 95% CI: 1.625-2.936). Conclusions: Anemia is significantly associated with poor neurological functional status in the short term in patients with ischemic cerebrovascular disease.